Nickel(0)‐Catalyzed Hydroalkenylation of Imines with Styrene and Its Derivatives - Xiao, Li‐Jun; Zhao, Chao‐Yue; Cheng, Lei; Feng, Bo‐Ya; Feng, Wei‐Min; Xie, Jian‐Hua; Xu, Xiu‐Fang; Zhou, Qi‐Lin (Angewandte Chemie, 2018)
A nickel(0)‐catalyzed hydroalkenylation of imines with styrene and its derivatives is described. A wide range of aromatic and aliphatic imines directly coupled with styrene and its derivatives, thus providing various synthetically useful allylic amines with up to 95 % yield. The reaction offers a new atom‐ and step‐economical approach to allylic amines by using alkenes instead of alkenyl‐metallic reagents. Experiments and DFT calculations showed that TsNH2 promotes the proton transfer from the coordinated olefin to the imine, accompanied by a new C−C bond formation. Ohne Metallreagentien: Die Nickel(0)‐katalysierte Hydroalkenylierung von Iminen mit Styrol und Styrolderivaten bietet einen neuen atomökonomischen und direkten Ansatz für die Synthese von Allylaminen ausgehend von Alkenen anstelle von Alkenylmetallreagentien. PG=Schutzgruppe, Ts=4‐Toluolsulfonyl.